Analisis Kebijakan Implementasi Upaya Khusus Sapi induk Wajib Bunting (UPSUS SIWAB) di Kota Jambi - Budi Jaya; Firmansyah Firmansyah; Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2021)
This study aims to determine the influence of communication factors, resources, disposition and bureaucracy on the implementation of the Upsus siwab program in Jambi City. This research was conducted on November 9, 2020 to December 5, 2020. The objects observed in this study were all officials and officers involved in the implementation of Upsus Siwab. The data obtained from this study are primary data and secondary data. Data were analyzed using path analysis. The results of the path analysis prove that the factors of communication, resources, disposition and bureaucracy have a significant effect on the implementation of Upsus Siwab in Jambi City. Resource factor is the factor that has the greatest influence on the implementation of Upsus Siwab in Jambi City, followed respectively by the disposition, bureaucracy and communication factors. All factors have a positive influence, meaning that the increase in the quality and quantity of resource factors, disposition factors, bureaucratic factors and communication factors will be followed by a positive increase from the implementation of Upsus Siwab in Jambi City. All factors interact with each other so that efforts to increase the implementation of Upsus Siwab in Jambi City are carried out by increasing resource factors, disposition factors, bureaucratic factors and communication factors. Based on this research, it can be concluded that the factors of communication, resources, disposition and bureaucracy affect the implementation of Upsus Siwab in Jambi City.